Pelargonidin ameliorates MCAO-induced cerebral ischemia/reperfusion injury in rats by the action on the Nrf2/HO-1 pathway - Fu Kong (De Gruyter, 2021)
Morbidity and mortality remain high for ischemic stroke victims, and at present these patients lack effective neuroprotective agents, which improve the cure rate. In recent years, studies have shown that pelargonidin has many biological actions. However, few studies are available regarding the pelargonidin treatment of cerebral ischemia.